Detection of severe acute respiratory syndrome coronavirus 2 in nasopharynx according to clinical phenotype of affected patients. (December 2020) - Valent, Francesca; Di Chiara, Antonio
Abstract: Objectives: Duration of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the upper respiratory tract is extremely variable, but its relation to disease severity is unknown. We investigated this relation in the 530 000 inhabitants of the northeastern Italian province of Udine. Methods: We analysed real-time RT-PCR tests for SARS-CoV-2 in upper respiratory specimens conducted at the Virology Laboratory of the University Hospital of Udine, Italy (which serves the whole province) from 1 March to 30 April 2020 Specimens were from positive individuals in four groups characterized by different disease severity (critically ill patients admitted to intensive care units, patients admitted to infectious disease units, symptomatic patients visiting the emergency department and not hospitalized, and asymptomatic individuals tested during contact tracing or screening activities). Duration of viral positivity was assessed from the first positive test to the day of the first of two consecutive negative tests. Univariate and multivariate analyses were conducted to investigate differences in the four groups. Results: From 1 March to 30 April, 39 483 RT-PCR tests for SARS-CoV-2 were conducted on 23 778 individuals, and 974 individuals had a positive test result. Among those with multiple tests ( n = 878), mean time to negativity was 23.7 days (standard error 0.3639; median 23, interquartile range 16–30 days). Mean time to negativity was longer in the group admitted to the intensive care unit than in the others, whereas no difference was observed between asymptomatic patients and those with mild disease. Conclusions: Disease control measures should not be adjusted to account for differences in viral shedding according to symptomatic status.